2021
DOI: 10.1155/2021/2220096
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of College English Mobile Learning Model Based on Distributed Terminal

Abstract: The quality of English teaching cannot be separated from the students’s accumulation and mastery of vocabulary, and sufficient vocabulary can ensure that students feel easy and comfortable in the language application. However, there are still some problems in teaching English vocabulary in colleges and universities, such as single presentation method, lack of real context, and other difficulties. With the rapid development of mobile Internet, the share of smart mobile devices among college students has increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Since most of the devices are acquired for different reasons including for academic purposes, students' motivations might vary between applying MLDs for entertainment/recreation and educational purposes. Conversely, the findings of this study relate to previous studies by Mohammadi et al (2020) and Wang and Lei (2021) who concluded that one reason students or users might use or apply MLDs is for recreational purposes, education, or a combination of both (edutainment) or even for gratification to circumvent boredom.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Since most of the devices are acquired for different reasons including for academic purposes, students' motivations might vary between applying MLDs for entertainment/recreation and educational purposes. Conversely, the findings of this study relate to previous studies by Mohammadi et al (2020) and Wang and Lei (2021) who concluded that one reason students or users might use or apply MLDs is for recreational purposes, education, or a combination of both (edutainment) or even for gratification to circumvent boredom.…”
Section: Discussionsupporting
confidence: 69%
“…Nowadays, language learning is also becoming a central feature in the adoption of MLDs. According to Wang and Lei (2021), the use of MLDs to teach English vocabulary to college students can be more effective when combined with mobile terminals-an integration of various MLDs in one space, allowing for the convenience of access to the learning material. In that context, Wang and Lei (2021) further submit that external sound enhancement devices like speakers could be installed to reinforce spoken word learning and enhance listening skills, which even extends to other relevant online content that comes in form of edutainment.…”
Section: Language Learning Through Mlds In Higher Educational Institu...mentioning
confidence: 99%
“…Users' mental health-related data is highly private, so it is necessary to set up a strong information security authentication mechanism to protect users' data from being leaked. In communication, this system adopts two-way authentication mechanism, that is, only authenticated users and authenticated mobile phone software can communicate with the back-end server [16]. Asymmetric encryption algorithm is used in the two-way authentication process, and symmetric encryption algorithm is used in the back-end server to encrypt and protect the user's private information.…”
Section: System Security Problem Solutionmentioning
confidence: 99%
“…The use of mobile information technology empowers modern learning styles with the advantages of autonomy, mobility, and readiness to effectively improve teaching and learning [9][10][11]. However, the integration of information technology and teaching cannot be achieved without relevant theoretical support as well as teaching practices [12]. Technology integration model is to assist teachers to use information technology, apply technology to all aspects of teaching and learning, and realize the deep integration of information technology and teaching [13][14][15].…”
Section: Introductionmentioning
confidence: 99%